2014
DOI: 10.1088/1367-2630/16/3/033040
|View full text |Cite
|
Sign up to set email alerts
|

Efficient quantum circuits for diagonal unitaries without ancillas

Abstract: The accurate evaluation of diagonal unitary operators is often the most resourceintensive element of quantum algorithms such as real-space quantum simulation and Grover search. Efficient circuits have been demonstrated in some cases but generally require ancilla registers, which can dominate the qubit resources. In this paper, we give a simple way to construct efficient circuits for diagonal unitaries without ancillas, using a correspondence between Walsh functions and a basis for diagonal operators. This corr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
88
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 86 publications
(91 citation statements)
references
References 23 publications
0
88
0
Order By: Relevance
“…Of course, the belief abouts uch difficulty with classical computers is based on well-known conjectures in computational complexity.H ere we consider ac lass of circuits known as IQP (instantaneousq uantum polynomial time), which was introduced in Refs. [60,61] In particular,w es tress that for any nqubit diagonal unitary D,u sing techniques from Ref. Equivalently one couldr egarda nI QP circuit as as equence of commuting quantum gates.…”
Section: Instantaneous Quantum Polynomial Timec Ircuitsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of course, the belief abouts uch difficulty with classical computers is based on well-known conjectures in computational complexity.H ere we consider ac lass of circuits known as IQP (instantaneousq uantum polynomial time), which was introduced in Refs. [60,61] In particular,w es tress that for any nqubit diagonal unitary D,u sing techniques from Ref. Equivalently one couldr egarda nI QP circuit as as equence of commuting quantum gates.…”
Section: Instantaneous Quantum Polynomial Timec Ircuitsmentioning
confidence: 99%
“…[35,36].A nn-qubit IQP circuit takes the form H n DH n where D is adiagonal unitaryoperator. [61] we could construct an approximation circuitD acting on the same n qubitsu sing only nearest neighborC NOT gates (see Section 6). As simple as they seem, the output distributions of IQP circuits are classically hard to sample from in the worst case.…”
Section: Instantaneous Quantum Polynomial Timec Ircuitsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, this work sparked the development of quantum algorithms for the required task of quantum state preparation (Kassal et al, 2008), and similar approaches which handle multi-reference states (Wang et al, 2008). Researchers have also considered extending the use of quantum algorithms to various regimes in quantum chemistry such as relativistic dynamics (Veis et al, 2012) and quantum dynamics beyond the Born-Oppenheimer approximation (Kassal et al, 2008;Welch et al, 2014;. Error correction for quantum algorithms for quantum chemistry has also been investigated (Jones et al, 2012).…”
Section: Q U a N T U M A L G O R I T H M S A N D Protocols For Chemistrymentioning
confidence: 99%
“…Subsequent works have opened up an entire line of inquiry concerning real-space simulation of quantum chemistry (Kassal et al, 2008;Welch et al, 2014;Kivlichan et al, 2016). In particular, it has been found that for systems with more than roughly 4 atoms, real space simulation is both more efficient and more accurate than second-quantized methods (Kassal et al, 2008;Kivlichan et al, 2016).…”
Section: Q U a N T U M A L G O R I T H M S A N D Protocols For Chemistrymentioning
confidence: 99%